A case report of atrial fibrillation in a patient with heparin resistance associated with an antithrombin III deficiency successfully treated by radiofrequency catheter ablation using a direct thrombin inhibitor. Issue 1 (9th January 2019) - Kang, Honsa; Takemoto, Masao; Tayama, Kei-ichiro; Kosuga, Ken-ichi
Abstract: Background: Pulmonary vein antrum isolation has proven to be a useful strategy for radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF) worldwide. Anticoagulation therapies are necessary to avoid thromboembolic events before, during, and after RFCA of AF. During the RFCA procedure for AF, it is recommended that the activated coagulation time be maintained between 300 s and 400 s using heparin as an anticoagulation therapy. Case summary: An 81-year-old man with symptomatic and drug-refractory paroxysmal AF underwent RFCA. We found that he had a severe heparin resistance during the RFCA procedure, and heparin had little effect on him. Thus, a direct thrombin inhibitor, Argatroban Hydrate ®, was used instead of heparin for anticoagulation therapy during the procedure. Finally, the AF was successfully treated by RFCA without any complications. With a post-procedural inspection, we found that he had a Type-1 antithrombin III (AT-III) deficiency. Discussion: Atrial fibrillation is the most common clinical arrhythmia and is associated with significant clinical morbidity and increased mortality. An AT-III deficiency is a well-known autosomal dominant hereditary disease and congenital blood coagulation abnormality occurring in about 1:500–5000 live births that may sometimes cause thrombophilia. Thus, the physicians may occasionally come across patients with an AT-III deficiency in real-world clinical practice, even though they have no history of thrombophilia. Argatroban Hydrate ® may be effective and feasible for anticoagulation therapy during the RFCA procedure of AF in patients with heparin resistance such as in this present case.